PEMBENTUKAN PELATIHAN LAPANGAN KERJA UNTUK NARAPIDANA YANG TELAH BEBAS: UPAYA UNTUK MENGURANGI ANGKA RESIDIVIS - Saputra, Jefryan Mahardika (Jendela Inovasi Daerah, 2024)
In an effort to reduce the recidivism rate among prisoners who have been released, the establishment of job training is a potential innovation. This training is designed to provide skills and knowledge that can increase employment opportunities and reduce the likelihood of re-engagement in criminal activity. This research aims to evaluate the effectiveness of establishing job training for released prisoners in reducing recidivism rates. Involves literature analysis to understand the concepts and results of previous research related to the establishment of job training for prisoners. The findings of this research indicate that job training programs can be adapted to provide relevant and useful training by thoroughly understanding the needs of prisoners, such as skills needs, psychosocial support, cross-sector collaboration, life motivation, work readiness, and community integration. The success of this program depends on cooperation between Corrections, local government, and the private sector. With the involvement of the private sector, training can be tailored to the demands of the workforce. In addition, the skills acquired during training can increase the chance of getting a job and build social stability. The establishment of job training for released prisoners could be a positive step in addressing the problem of recidivism. Implementation of these programs can help create a positive impact in preparing inmates for successful reintegration into society and the job market.